UJI EFEK ANTIINFLAMASI EKSTRAK HERBA SURUHAN (Peperomia pellucida L. KUNTH) PADA TIKUS PUTIH JANTAN - Sumi Wijaya; Monica S.W (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2004)
Peperomia pellucida L. Kunth herbs (Herba Suruhan) is one of the alternative for inflamation therapy. In this study, albino rats were devided into seven groups. The first three groups was administered orally the extract of Suruhan herbs 1500 mg/Kg body weight, 2000 mg/Kg body weight and 2500 mg/Kg body weight. The next three groups were given Indomethacine solutions with the doses of 13.5 mg/Kg body weight, 15.8 mg/Kg body weight and 15 mg/Kg body weight, and the last groups (control) were given 1% of PGA suspension alone. Fifty microliter of Carrageen solution of 1.5% was injected subcutaneously to all rats in those group.The volume of the foot paw of albino male rat injected with carrageen, was measured and recorded for 4 hours. The number of leucocyte and the number of differential count were observed every two hour, namely at the fourth, sixth and eight hours following carrageen injection. There were significant differences in the antiinflamation effect using plethysmometer and the number of leucocyte counts between control and all the treatment group. For the differential count, not all the results showed significant differences.